2023
DOI: 10.1111/cch.13171
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in early child development in children aged under 36 months in South Asia: A systematic review

Damith Chandrasenage,
Oonagh Markey,
William Johnson
et al.

Abstract: BackgroundIn South Asia, 89 million children under 5 are at risk of not reaching their developmental potential. Household socioeconomic position (SEP) is a determinant of early child development (ECD). However, synthesised evidence for the association between ECD and SEP in young children in South Asia is not available. Therefore, this review synthesises evidence on the relationship of household SEP with ECD in children under 36 months of age in South Asia.MethodPubMed, Cochrane Library, MEDLINE and Scopus wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…The increased inequality in these regions can be attributed to constrained access to quality education and human capital development, challenges in land ownership and agrarian structures. Varying degrees of industrialisation and urbanisation, coupled with potential labour exploitation, also play a role 39. These underlying factors may exert an indirect impact on MDD, as evidenced in our study by the observed lower attainment rate 34 35…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The increased inequality in these regions can be attributed to constrained access to quality education and human capital development, challenges in land ownership and agrarian structures. Varying degrees of industrialisation and urbanisation, coupled with potential labour exploitation, also play a role 39. These underlying factors may exert an indirect impact on MDD, as evidenced in our study by the observed lower attainment rate 34 35…”
Section: Discussionmentioning
confidence: 57%
“…Varying degrees of industrialisation and urbanisation, coupled with potential labour exploitation, also play a role. 39 These underlying factors may exert an indirect impact on MDD, as evidenced in our study by the observed lower attainment rate. 34 35 …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation